Physicochemical Changes of Cocoa Beans during Roasting Process - Pedro García-Alamilla; Laura Mercedes Lagunes-Gálvez; Juan Barajas-Fernández; Ricardo García-Alamilla (Journal of Food Quality)
During cocoa beans roasting, there are physicochemical changes that develop the chocolate quality attributes. Roasting systems have a particular influence on the development of these characteristics, and the effects of operation variables for each system must be evaluated. The objective of this study was to evaluate the effect of roasting time and temperature in a rotatory system on cocoa beans physicochemical parameters of quality as moisture, water activity, pH, total acidity, color (L⁎,a⁎,b⁎), total phenolic content (TPC), and DPPH radical capacity. Cocoa beans were roasted as a function with a central rotatable design with 22 + 5 central points and 4 axial points (-1.414, -1, 0, +1, and +1,414) and a response surface methodology was applied. Temperature and time levels were 110–170°C and 5–65 minutes, respectively. The effect of the variables was nonlinear and modeled with a second-order response polynomial. Roasting time and temperature presented a significative effect (p<0.05) on the response variables except for both TPC and DPPH radical capacity in aqueous extract.